2017
DOI: 10.1159/000484720
|View full text |Cite
|
Sign up to set email alerts
|

High Systolic Blood Pressure after Successful Endovascular Treatment Affects Early Functional Outcome in Acute Ischemic Stroke

Abstract: Background: Endovascular treatment (EVT) has been shown to significantly improve functional outcome in patients with acute large cerebral vessel occlusions. To date, no evidence-based recommendations on blood pressure management after successful EVT exist. Previous studies showed an association between high pre-EVT systolic blood pressure (SBP) and functional outcome, but do not answer the question on how to manage blood pressure after successful recanalization. The purpose of this study was to determine the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Although our study did not find the maximum SBP to be an influential factor for functional outcome, this may be related to our study subjects' characteristics. Our research found that the rate of successful recanalization was higher in the favorable outcome group, which also had lower maximum SBP, indirectly suggesting that patients with successful reperfusion are more likely to benefit from lower SBP [26].…”
Section: Discussionmentioning
confidence: 53%
“…Although our study did not find the maximum SBP to be an influential factor for functional outcome, this may be related to our study subjects' characteristics. Our research found that the rate of successful recanalization was higher in the favorable outcome group, which also had lower maximum SBP, indirectly suggesting that patients with successful reperfusion are more likely to benefit from lower SBP [26].…”
Section: Discussionmentioning
confidence: 53%
“…[ 45 ] Numerous studies have confirmed that hypertension and high blood pressure are associated with sICH and poor functional outcome in acute ischaemic stroke, [ 46 , 47 ] and higher maximum SBP was also associated with poor functional outcomes after MT. [ 36 ] The post hoc data analysis of the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischaemic Stroke in the Netherlands reported that BP did not affect the benefit or safety of MT in patients with AIS, but it also confirmed a strong correlation between systolic blood pressure and functional outcomes in ischaemic stroke, and the association was U-shaped. Both low and high baseline mean SBP measurements were associated with poor functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that the rate of successful recanalization was higher in the favorable outcome group, which also had lower maximum SBP. Patients with successful reperfusion are more likely to benefit from lower SBP [19]. Some studies showed that BP within the first 48 hours after a stroke showed a U-shaped correlation with clinical outcome [17,20], particularly in patients with non-recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 64.8±10.9 years, and 27 (37.5%) were women. The median NIHSS score at admission was 14 points [IQR, [9][10][11][12][13][14][15][16][17][18][19], while the median ASPECTS was 8 points [IQR, [7][8][9]. Of the 72 patients, 86.1% patients achieved recanalization (TICI 2b or 3).…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 99%